2017
DOI: 10.22146/bkm.25783
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh aktivitas fisik terhadap kejadian hipertensi pada pekerja (Analisis data Riskesdas 2013)

Abstract: Purpose:  This research aimed to know the influence of physical activity and external variables on hypertension in workers. Methods: We used secondary data for our research which is Basic Health Research (Riskesdas) 2013. The total population was 1,027,763. Our inclusion criteria were: have a main job, aged ≥15 years, measured height, measured weight, measured abdominal circumference, measured blood pressure, and not pregnant. We found 371,713 respondents matching our criteria. We analyzed our data using chi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 0 publications
2
12
0
11
Order By: Relevance
“…This study reported that 21 respondents (37.50%) as the largest group of hypertensive patients were unemployed, 18 respondents (32.14%) work as a labor. Hardati & Ahmad (2017) presented similar findings, unemployed individuals are 8.95 times at risk for hypertension compared to employed population. People with less physical activity characterized by Metabolic Equivalent Task (MET) lower than 600 per week were 1.25 times at greater risk of experiencing hypertension compared to individuals with physical activity more than 600 MET per week.…”
Section: Difference Of the Two Mean Map Values In The Control Groupsupporting
confidence: 67%
“…This study reported that 21 respondents (37.50%) as the largest group of hypertensive patients were unemployed, 18 respondents (32.14%) work as a labor. Hardati & Ahmad (2017) presented similar findings, unemployed individuals are 8.95 times at risk for hypertension compared to employed population. People with less physical activity characterized by Metabolic Equivalent Task (MET) lower than 600 per week were 1.25 times at greater risk of experiencing hypertension compared to individuals with physical activity more than 600 MET per week.…”
Section: Difference Of the Two Mean Map Values In The Control Groupsupporting
confidence: 67%
“…The results showed that the lifestyle of patients who did physical activity/sports was 68.1%. Physical activity or sports are part of the risk of hypertension (Hardati and Ahmad, 2013). The results also showed that patients who did a diet were 66.0%.…”
Section: Results and Discussion Patient Characteristics Datamentioning
confidence: 84%
“…Sementara itu hasil penelitian dengan menggunakan data sekunder lainnya menunjukkan hal yang serupa, penelitian Hardatipada 371.713 penduduk berusia ≥15 tahun menggunakan data Riskesdas tahun 2013 juga menemukan hubungan yang signifikan antara aktivitas fisik dengan hipertensi (P-value 0,000). Penduduk yang kurang aktivitas fisik lebih berisiko 1,25 kali mengalami hipertensi dibandingkan penduduk yang cukup aktivitas fisik (POR: 1,25; 95 % CI: 1,21-1,28), setelah dikontrol oleh variabel umur, obesitas, konsumsi makanan berlemak, merokok dan stress, risikonya menjadi 1,08 (POR: 1,25; 95% CI: 1,05-1,11) (Hardati, 2017).…”
Section: Hasil Dan Pembahasanunclassified
“…Melakukan aktivitas secara teratur (aktivitas fisik aerobik selama 30-45 menit/hari) diketahui sangat efektif dalam mengurangi risiko hipertensi hingga mencapai 19%-30%, sementara rendahnya kebugaran kardiorespirasi terutama pada usia lanjut diduga dapat meningkatkan risiko hipertensi sebesar 50% (Hardati, 2017).Peningkatan aktivitas fisik akan mengurangi risiko untuk menderita hipertensi dimasa depan (Juraschek dkk., 2014).Sementara orang-orang yang kurang aktivitas fisik cenderung mempunyai detak jantung yang lebih tinggi, semakin tinggi detak jantung maka semakin keras jantung harus bekerja untuk setiap kontraksi dan semakin kuat desakan pada dinding arteri (Tseng dkk., 2012).…”
Section: Hasil Dan Pembahasanunclassified